How does job insecurity cause unethical pro-organizational behavior? The mediating role of impression management motivation and the moderating role of organizational identification - Xu, Lin; Wen, Ting; Wang, Jigan (Frontiers in Psychology, 2022)
This study aims to examine the effect of quantitative and qualitative job insecurity on unethical pro-organizational behavior (UPB), focusing on the mediating effect of impression management motivation and the moderating effect of organizational identification. A two-wave questionnaire survey is conducted, and data from 254 employees of Chinese enterprises are used to test the research hypotheses. Empirical results show that: (1) Quantitative job insecurity has a significant positive effect on UPB, while positive effect of qualitative job insecurity on UPB is insignificant. (2) Quantitative job insecurity positively affects impression management motivation and increases UPB. Although the direct effect of qualitative job insecurity on UPB is insignificant, it positively affects UPB through impression management motivation. (3) Organizational identification plays a positive moderation role in the relationship between impression management motivation and employees’ UPB, that is, high-degree organizational identification leads to a strong effect of impression management motivation on UPB; furthermore, organizational identification moderates the mediating role of impression management motivation in the relationships between quantitative, qualitative job insecurity, and UPB, such that the effect is strong when organizational identification is high, rather than low. This study compares the effect of quantitative and qualitative job insecurity on employees’ UPB, reveals that impression management motivation is the key mechanism of quantitative and qualitative job insecurity affecting UPB, and points out the moderating effect of organizational identification, which offers implications for organizational management practices.